2010
DOI: 10.1007/s12542-010-0082-9
|View full text |Cite
|
Sign up to set email alerts
|

New early Jurassic decapod crustacean from Patagonia (Chubut province), Argentina

Abstract: A well-preserved decapod specimen was found in early Toarcian deposits cropping out on the western slope of Meseta Catreleo, central Chubut province, Argentina. It is a nearly complete exoskeleton preserved in lateral view, slightly crushed, in fine-grained sandstones. The skeleton is mostly articulated, though some pieces are disarticulated or missing. Taphonomic features indicate a relatively rapid burial after death, with little or no transport. This specimen is here described as a new species of the genus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Preliminary biostratigraphic analyses carried out in the southern and west-central Chubut Province (Pagani et al, 2012;Ferrari, 2013Ferrari, , 2014a indicated a late Pliensbachian-early Toarcian age for these deposits. Moreover, Damborenea and Ferrari (2008), Ferrari (2009Ferrari ( , 2011aFerrari ( , b, 2012Ferrari ( , 2013Ferrari ( , 2014a, Ferrari et al (2014) and Pagani et al (2011Pagani et al ( , 2012 recently carried out new studies on the taxonomic composition of the faunas in the Early Jurassic of south-western and central Chubut Province, including the investigation of new fossil localities and the collection of Early Jurassic material.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…Preliminary biostratigraphic analyses carried out in the southern and west-central Chubut Province (Pagani et al, 2012;Ferrari, 2013Ferrari, , 2014a indicated a late Pliensbachian-early Toarcian age for these deposits. Moreover, Damborenea and Ferrari (2008), Ferrari (2009Ferrari ( , 2011aFerrari ( , b, 2012Ferrari ( , 2013Ferrari ( , 2014a, Ferrari et al (2014) and Pagani et al (2011Pagani et al ( , 2012 recently carried out new studies on the taxonomic composition of the faunas in the Early Jurassic of south-western and central Chubut Province, including the investigation of new fossil localities and the collection of Early Jurassic material.…”
Section: Introductionmentioning
confidence: 93%
“…The stratigraphy of these deposits has been established by several studies. An updated and detailed historical chronology of the Jurassic stratigraphic sequence of this region in Patagonia was recently provided by Ferrari (2009Ferrari ( , 2011aFerrari ( , b, 2013Ferrari ( , 2014a and Pagani et al (2011).…”
Section: Geological Settingmentioning
confidence: 99%
See 3 more Smart Citations